2007
DOI: 10.1016/j.ydbio.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Bmp4 regulates left–right asymmetry at two distinct developmental time points

Abstract: Left-right (LR) asymmetry is regulated by early asymmetric signals within the embryo. Even though the role of the bone morphogenetic protein (BMP) pathway in this process has been reported extensively in various model organisms, opposing models for the mechanism by which BMP signaling operates still prevail. Here we show that in zebrafish embryos there are two distinct phases during LR patterning in which BMP signaling is required. Using transgenic lines that ectopically express either noggin3 or bmp2b, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
226
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(243 citation statements)
references
References 48 publications
14
226
2
1
Order By: Relevance
“…Embryos and adult fish were raised and maintained under standard laboratory conditions. We used the following mutant and transgenic lines: laf/alk8 tm110 (23), Tg(ins:GFP) zf5 (38), Tg(ins:dsRed) m1018 (from W. Driever, Freiburg), Tg(HSE:caAlk6, eGFP) w64 (19), Tg(gutGFP) s854 (also known as Tg(XlEef1a1:GFP) s854 ) (15), Tg(hsp70l:bmp2b) f13 (39), Tg(ptf1a:GFP) jh1 (40), and Tg(-3.5nkx2.2a:GFP) ia3/ia3 (41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryos and adult fish were raised and maintained under standard laboratory conditions. We used the following mutant and transgenic lines: laf/alk8 tm110 (23), Tg(ins:GFP) zf5 (38), Tg(ins:dsRed) m1018 (from W. Driever, Freiburg), Tg(HSE:caAlk6, eGFP) w64 (19), Tg(gutGFP) s854 (also known as Tg(XlEef1a1:GFP) s854 ) (15), Tg(hsp70l:bmp2b) f13 (39), Tg(ptf1a:GFP) jh1 (40), and Tg(-3.5nkx2.2a:GFP) ia3/ia3 (41).…”
Section: Methodsmentioning
confidence: 99%
“…To further test this model, we treated Tg(ins:GFP);Tg(ins:dsRed) embryos with dorsomorphin (a selective inhibitor of the BMP type I receptors Alk3, Alk6, and Alk8, see ref. 39) between 44 and 72 hpf to inhibit Bmp signaling specifically during the formation of ventral bud-derived endocrine cells (this time period was chosen to allow budding of the ventral pancreas, but inhibit Bmp signaling during subsequent ventral bud development). We found that the number of GFP-only-positive β-cells adjacent to the extrapancreatic duct was increased in the dorsomorphin-treated embryos ( Fig.…”
Section: Differential Requirement For Bmp Signaling During Ventral Pamentioning
confidence: 99%
“…6B). This reflects the requirement of bmp4 for left-sided expression of spaw, which in turn induces left-sided expression of bmp4 and lefty1, whereas lefty1 and lefty2 negatively regulate each other (Bisgrove et al, 1999;Chocron et al, 2007;Bakkers et al, 2009). To examine if these effects are early or late events in cardiogenesis, we examined bmp4 expression at sphere, shield and 48 hpf in addition to the 18-somite stage by qRTPCR.…”
Section: Role Of Plakophilin 2 In Cardiogenic Gene Expressionmentioning
confidence: 99%
“…BMPs have been implicated in LR patterning, but data on their precise roles have been highly contradictory, with results varying both within and between developmental models Yokouchi et al 1999;Monsoro-Burq and Le Douarin 2001;Fujiwara et al 2002;Piedra and Ros 2002;Schlange et al 2002;Kishigami et al 2004;Zhu and Scott 2004;Chocron et al 2007;Mine et al 2008). This is in part because BMPs act at distinct times and in distinct spatial domains to influence laterality (Kishigami et al 2004).…”
mentioning
confidence: 99%